Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Solve each system by elimination
-3x-6y=-3
5x+5y=0


Sagot :

Answer:

x=1 and y=−1

Step-by-step explanation:

Multiply the first equation by 5,and multiply the second equation by 6.

5(−3x−6y=3)

6(5x+5y=0)

Becomes:

−15x−30y=15

30x+30y=0

Add these equations to eliminate y:

15x=15

Then solve15x=15for x:

15x=15

15x

15

=

15

15

(Divide both sides by 15)

x=1

Now that we've found x let's plug it back in to solve for y.

Write down an original equation:

−3x−6y=3

Substitute1forxin−3x−6y=3:

(−3)(1)−6y=3

−6y−3=3(Simplify both sides of the equation)

−6y−3+3=3+3(Add 3 to both sides)

−6y=6

−6y

−6

=

6

−6

(Divide both sides by -6)

y=−1